Unethical Conduct And Performance Of Microfinance Institutions in (SACCOs) Uganda - Otai Isaac Peter (Journal of Economics and Business Aseanomics, 2024)
Savings and Credit Cooperative Societies (SACCOS) are co-operatives of financial nature whose aim is to encourage savings, extend loans and other services of financial nature to its associates and improve their income and living conditions. However, the ability of SACCOs to achieve these roles is influenced by so many factors. This paper, therefore aims at examining the relationship between unethical conduct proxied as excessive lending interest rates, forceful loan recovery practices and coercive lending techniques, and the performance of microfinance institutions; a case of SACCOs in Kumi district, Uganda. The study adopted descriptive design and questionnaires were used to gather data. Data was analyzed by use of inferential statistics. Findings revealed that excessive lending interest rates had negative insignificant association while forceful loan recovery practices and coercive lending techniques had positive insignificant relationship with performance of SACCOs. The study recommends that microfinance regulatory bodies like Uganda Microfinance Regulatory Authority and Association of Microfinance Institutions in Uganda, use these findings to understand factors affecting performance of microfinance institutions so as to promote sound practices among practitioners and industry cohesion.